Affected Sib-Pair Analyses Identify Signaling Networks Associated With Social Behavioral Deficits in Autism - Pirooznia, Mehdi; Niranjan, Tejasvi; Chen, Yun-Ching; Tunc, Ilker; Goes, Fernando S.; Avramopoulos, Dimitrios; Potash, James B.; Huganir, Richard L.; Zandi, Peter P.; Wang, Tao (Frontiers in Genetics, 2019)
Autism spectrum disorders (ASDs) are characterized by deficits in three core behavioral domains: reciprocal social interactions, communication, and restricted interests and/or repetitive behaviors. Several hundreds of risk genes for autism have been identified, however, it remains a challenge to associate these genes with specific core behavioral deficits. In multiplex autism families, affected sibs often show significant differences in severity of individual core phenotypes. We hypothesize that a higher mutation burden contributes to a larger difference in the severity of specific core phenotypes between affected sibs. We tested this hypothesis on social behavioral deficits in autism. We sequenced synaptome genes (n=1,886) in affected male sib-pairs (n=274) in families from the Autism Genetics Research Exchange (AGRE) and identified rare (MAF≤1%) and predicted functional variants. We selected affected sib-pairs with a large (≥10; n=92 pairs) or a small (≤4; n=108 pairs) difference in total cumulative Autism Diagnostic Interview-Revised (ADI-R) social scores (SOCT_CS). We compared burdens of unshared variants present only in sibs with severe social deficits and found a higher burden in SOCT_CS≥10 compared to SOCT_CS≤4 (SOCT_CS≥10: 705.1±16.2; SOCT_CS≤4, 668.3±9.0; p=0.025). Unshared SOCT_CS≥10 genes only in sibs with severe social deficits are significantly enriched in the SFARI gene set. Network analyses of these genes using InWeb_IM, MSigDB, and GeNetMeta identified enrichment for PI3K-AKT-mTOR (eScore P-value=3.36E-07; n=8 genes) and NGF (eScore P-value =8.94E-07; n=9 genes) networks. These studies support a key role for these signaling networks in social behavioral deficits and present a novel approach to associate risk genes and signaling networks with core behavioral domains in autism.